ANALISIS KOMUNIKASI PERSUASIF PADA AKUN YOUTUBE USTADZ HILMAN FAUZI (Studi Penerimaan pada Penonton Youtube Ustadz Hilman Fauzi): Studi Penerimaan pada Penonton Youtube Ustadz Hilman Fauzi - Suci, Yananti Putri; Akhyar, Taufik; Azarkasyi, Badarudin (Jurnal Prodi Ilmu Komunikasi, 2024)
Dakwah today does not only have to be delivered at recitations or events commemorating Islamic days, and does not always take place in mosques, ta'lim assemblies or other places. Da'wah delivered today can be conveyed through social media, one of which is YouTube. One of the preachers who utilizes social media YouTube as a means of preaching is Ustadz Hilman Fauzi, where he has a personal YouTube channel which often uploads da'wah content in the form of religious lectures. This study aims to analyze persuasive communication messages and YouTube audience acceptance of da'wah messages on Ustadz Hilman Fauzi's YouTube videos. The method used in this study is a qualitative method based on the reception analysis theory approach. Sources of data obtained from the results of documentation, observation and in-depth interviews. The results of the study show that there are several dominant messages displayed in Ustadz Hilman Fauzi's YouTube videos. Then the informants had various acceptances of the dominant discourse offered and were classified into three different positions, namely dominant positions, negotiations and opposition.